(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the content, main directions, and international consequences of the "appeasement policy" pursued by British Prime Minister Neville Chamberlain in the 1930s. The appeasement policy aimed to reduce the risk of war by avoiding decisive action against the aggressive actions of German leader Adolf Hitler, opting instead for compromise. The article highlights the Munich Agreement, the occupation of the Sudetenland, and how this policy was directly linked to the outbreak of the Second World War. Throughout the analysis, both the positive and negative aspects of the policy are considered in a balanced manner, with Chamberlain’s decisions evaluated within the historical context. The article includes a scholarly approach and independent conclusions on this relevant topic in historiography.